Designing a self-associated cationic polymer for enhanced compatibility, palatability, and gastric release of cefuroxime axetil - Menjoge, Anupa R.; Kulkarni, Mohan G. (Biomacromolecules, 2007)
Cefuroxime axetil (CA) has exhibited interactions with the polymers hydroxypropyl methylcellulose phthalate, cellulose acetate trimellitate, and Eudragit E resulting in the generation of unacceptable amounts of impurities and degradation. Formulations, which mask the bitter taste of CA and release it immediately in the stomach, have therefore not been possible. In an attempt to overcome the interaction with CA, we report a self-associated cationic polymer (NREP) containing methyl methacrylate (MMA), 2-hydroxy ethylmethacrylate (HEMA), and 4-vinyl pyridine (4-VP). The hydrogen bonding between the pyridine nitrogen and the hydroxyl groups of HEMA results in strong intrachain associations, prevents interactions between NREP and CA, and inhibits degradation of CA. This has been validated by differential scanning calorimetry, Fourier transform infrared spectroscopy, NMR, and high-performance liquid chromatography analysis. These self-associations restrict polymer chain motions, enhance biocompatibility, and lead to a higher T-g, which ensures that NREP does not become tacky in processes involving heat. The judicious choice of the hydrophobic and hydrophilic monomers renders the polymer hydrophobic enough as to mask the bitter taste of CA at near neutral pH. Incorporation of the basic monomer 4-VP ensures rapid dissolution of the polymer and release of CA at the acidic pH prevalent in the stomach. The work indicates an approach to design pH-sensitive polymers for dosage forms that meet the pharmacokinetic requirements of the drug.

Hydrogen bonding in trivinyl monomers: implications for inclusion complexation and polymerization - Satav, Sunita S.; Karmalkar, Rohini N.; Kulkarni, Mohan G.; Mulpuri, Nagaraju; Sastry, G. Narahari (Macromolecules, 2007)
Trimethylolpropane trimethacrylate (TMPTMA) formed a 1:2 inclusion complex (IC) with beta-cyclodextrin (beta-CD). Polymerization of the complex resulted in a soluble, linear polymer containing two pendant unsaturations per repeat unit since the methacryloyl groups included in the beta-CD cavity did not react with the growing radical chain. Trimethylolpropane triacrylate (TMPTA) formed a 1:1 complex with beta-CD. Yet a soluble polymer containing two pendant unsaturations per repeat unit was obtained. Computational analysis confirmed that in TMPTA hydrogen bonding between C-H center dot center dot center dot O=C brings two acryloyl groups in close vicinity of one another. As a result, both acryloyl groups were included in the same beta-CD cavity. Trimethylolpropane diacrylate 4-vinylbenzoate (TMPDAVB) once again formed 1:2 IC as a result of disruption of hydrogen bonds between two acryloyl groups. The study highlights that an understanding of the composition of the IC is more important than its stoichiometry alone.

Template assisted highly ordered novel self assembly of micro-reservoirs and its replication - Hire, Santosh L.; Shelke, Manjusha V.; Kale, Vinayak S.; Galopin, Elisabeth; Kulkarni, Mohan G.; Boukherroub, Rabah; Ogale, Satishchandra B. (Lab on a Chip, 2010)
A novel method is developed for template assisted fabrication of a regular assembly of microcavity arrays. Simple micropatterns on PDMS mold are used to create complex geometries via solvent vapor back pressure in a biodegradable polymer. Cavities are in turn replicated in complimentary PDMS mushroom like microstructures.

Synthesis and characterization of bile acid-based poly beta amino esters for paclitaxel delivery - Gangwal, Jitendra J.; Kulkarni, Mohan G. (Journal of Applied Polymer Science, 2011)
New biodegradable poly beta amino esters were synthesized by the polymerization of Deoxycholic acid (DOCA) in all the structural planes by 1, 4 addition of Trimethylene dipiperidine (TMDP) to diacrylates of Deoxycholyl glycol, Methyl deoxycholate and Trimethylolpropane deoxycholate esters. H-1-NMR, C-13-NMR and IR studies confirmed presence of amine and Deoxycholyl units in polymers. XRD and TGA studies indicated that all the polymers were amorphous and thermostable up to 300 degrees C. DSC studies revealed glass transition temperature (T-g) in the range 70-80 degrees C. All the polymers degraded very slowly in the buffers of pH 1.1, 7.4 and 10 because of the hydrophobic nature of Deoxycholate units. These polymers also exhibited pH sensitivity due to the incorporation of amines along with Deoxycholate units in the backbone. P-Nitroaniline (PNA) release followed anomalous release kinetics. Paclitaxel (PTX) loaded nanospheres prepared from these polymers were spherical and uniform in the size range 75-250 nm and 0.4-1 mu depending upon the method of preparation. PTX loading was in the range 60-90%, while release (up to 20-60%) was sustained over a period of 100 h. (c) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 220-232, 2011
Keywords: bile acid; biodegradable; Nanoparticles; Paclitaxel; poly beta amino esters

One pot room temperature synthesis of robust gold nanochains - Biradar, Satish C.; Kulkarni, Mohan G. (RSC Advances, 2013)
We report a room temperature reduction and stabilization of gold nanoparticles (AuNPs) from auric chloride in the presence of 1.5 and 3 mM linear poly(amidoamine) (PAmAm), which leads to 1D assembly of AuNPs. At higher concentrations, isolated AuNPs are formed. Detailed investigations show that the morphology is governed primarily by pH rather than concentration. This is the first report to demonstrate the stability of nanochains against pH switching. The nanochains are robust as revealed by stability at higher temperature, salt concentration, thiol exchange, and would be useful in developing electronic devices for biological applications.